Electromagnetic Waves Dispersion and Interaction of an Annular Beam-Ion Channel System in Plasma Waveguide - Jixiong Xiao; Zhijiang Wang; Jun Chen; Changhai Liu (Advances in Mathematical Physics)
A linear theory for the electromagnetic properties and interactions of an annular beam-ion channel system in plasma waveguide is presented. The dispersion relations for two families of propagating modes, including the electrostatic and transverse magnetic modes, are derived. The dependencies of the dispersion behavior and interaction for different wave modes on the thickness of the annular beam and betatron oscillation frequency are studied in detail by numerical calculations. The results show that the inner and outer radii of the beam have different influences on propagation properties of the electrostatic and electromagnetic modes with different betatron oscillation parameters. In the weak ion channel situation, the two types of electrostatic waves, that is, space charge and betatron modes, have no interaction with the transverse magnetic modes. However, in the strong ion channel situation, the transverse magnetic modes will have two branches and a low frequency mode emerged as the new branch. In this case, compared with the solid beam case, the betatron modes not only can interact with the high frequency branch at small wavenumber but also can interact with the low frequency branch at large wavenumber.